Thoracic outlet syndrome: single-center experience on the transaxillary approach with the aid of the TRIMANO Arthrex arm - Mohammed Alkhani, MBBS; Matthieu Arsicot, MD; Alexandre Oliny, MD; Antoine Millon, MD, PhD; Nellie Della Schiava, MD, PhD; Marine Bordet, MD (Journal of Vascular Surgery Cases and Innovative Techniques, 2024)
Thoracic outlet syndrome (TOS) is a pathology caused by compression on the neurovascular bundle by the first rib. The treatment of TOS is conservative management by analgesia and physiotherapy; however, if there is no response to conservative treatment, surgery is indicated through thoracic outlet decompression by first rib resection. Several surgical techniques are available, including supraclavicular, transaxillary, and transthoracic first rib resection approaches. The transaxillary approach provides better visualization on the neurovascular bundle and, thus, is sometimes the preferred method of treatment. The transaxillary approach has been criticized due to safety concerns regarding the neural bundle during surgical exposure. During surgery, hyperabduction of the arm is obtained by a surgical assistant, and the quality of exposure can decrease with time, or an iatrogenic injury to the neural bundle (brachial plexus) can occur from the hyperabduction. The use of the TRIMANO Arthrex arm can help in the exposure, instead of a surgical aide, because it provides stable exposure and visualization for the operating surgeon. We performed a retrospective review of patients undergoing transaxillary first rib resection using the TRIMANO Arthrex arm between June 2021 and December 2022. During installation, the patient is placed in the lateral decubitus position and the TRIMANO Arthrex arm is fixed at the operating table at the height of the patient’s shoulder. Thus, the surgical aide can help the surgeon during the surgery, rather than placing the arm into and out of hyperabduction. The use of hyperabduction is limited to 15 minutes, followed by 5 minutes of rest, to decrease the tension on the neurovascular bundle. The surgeon then performs the transaxillary approach and systematically resects the first rib, scalene muscles, and subclavian muscles. By this approach, the inferior brachial plexus is also lysed. In our review, we found a total of 15 procedures of first rib resection for the treatment of TOS with the aid of the TRIMANO Arthrex arm that met our inclusion criteria. All procedures were performed by the same surgeon. None of the patients sustained an injury to the neurovascular bundle. All the patients had an uneventful hospital stay postoperatively, and none presented with a hematoma. The drain placed during surgery was removed on postoperative day 2. All patients had at least one radiograph taken during their hospitalization, with no pleural effusion or pneumothorax found. The use of the TRIMANO Arthrex arm is safe and can help in the positioning and installation of the patients undergoing transaxillary first rib resection. It decreases the number of surgical assistants and offers great comfort for the surgeon because it provides stable exposure for the operating surgeon.